2015
DOI: 10.1021/acs.jpcc.5b03923
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Synthetic Procedures on the Structural and Optical Properties of Mixed-Halide (Br, I) Perovskite Films

Abstract: The influence of thermal treatments on the properties of mixed bromide-iodide organolead perovskites (MAPbI3−xBrx, MA=CH3NH3) is investigated in films prepared in air by single-step solution processes based on different precursor solutions. Initially, the bandgap energy (EG) dependence on composition is reconsidered on films obtained by mixtures of tri-halide solutions.An EG(x) relation is obtained that is expected to be independent of the film properties and can be used to assess perovskite composition. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

11
98
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 82 publications
(109 citation statements)
references
References 52 publications
11
98
0
Order By: Relevance
“…Absorptiond egradation was found to correlate with increased full width at half maximum (FWHM) of the XRD peaks for mixed halide perovskites compared to MAPbI 3 and MAPbBr 3 (Figure 5a nd Ta ble 1). As imilar behavior of the FWHM of the XRD peaks was observedi n MAPb(I 1Àx Br x ) 3 films by Fedeli et al, [14] who also observed correlated changes in the Urbach energy,w hich may be related to structurald isorder.F urthermore, both Fedeli et al [14] and Sadhanala et al [10] found that changes in the FWHM of PL peaks were correlated with the Urbach energy variations, that is, the band-to-band PL peak becamen arrower when the Urbach energy was smaller (less structurald isorder) at low and high x values, and vice versa at intermediate x values. The decreasedg rain sizes in the mixed halide films (inc ompar- ison with those in MAPbI 3 and MAPbBr 3 samples) have been confirmed by scanning electron microscopy ( Figure S4).…”
supporting
confidence: 67%
See 4 more Smart Citations
“…Absorptiond egradation was found to correlate with increased full width at half maximum (FWHM) of the XRD peaks for mixed halide perovskites compared to MAPbI 3 and MAPbBr 3 (Figure 5a nd Ta ble 1). As imilar behavior of the FWHM of the XRD peaks was observedi n MAPb(I 1Àx Br x ) 3 films by Fedeli et al, [14] who also observed correlated changes in the Urbach energy,w hich may be related to structurald isorder.F urthermore, both Fedeli et al [14] and Sadhanala et al [10] found that changes in the FWHM of PL peaks were correlated with the Urbach energy variations, that is, the band-to-band PL peak becamen arrower when the Urbach energy was smaller (less structurald isorder) at low and high x values, and vice versa at intermediate x values. The decreasedg rain sizes in the mixed halide films (inc ompar- ison with those in MAPbI 3 and MAPbBr 3 samples) have been confirmed by scanning electron microscopy ( Figure S4).…”
supporting
confidence: 67%
“…[15,16] The E g values for MAPbI 3 and MAPbBr 3 samples are in agreement with previously reported ones (i.e., 1.58 [17] and 2.3 eV, [18 ] respectively). Sadhanala et al [10] and Fedeli et al [14] confirmed that the ratios of Br to Ii nt heir MAPb(I 1Àx Br x ) 3 films are the same as those in the solutionsw hen as toichiometric precursor compositioni n as ingle deposition step was used. We concludet hat the mixed halide films have asinglephase structure (solid solution)with Br contentslightly larger than that expected from the precursor materials, probablyo wing to the sequential, two-step deposition method (see the Experimental Sectionf or details).…”
mentioning
confidence: 88%
See 3 more Smart Citations